The effects of different treatments of seed priming and foliar application of nano particle and zinc sulphate on agronomic traits in safflower - اکبر شفیعی; نورعلی ساجدی; مهدی چنگیزی (علوم و فناوری بذر ایران)
In order to study effects of seed priming and foliar application of nano particle and zinc sulfate on yield and yield components of safflower, an experiment was carried out  based on RCBD  with four replications in Islamic Azad University, Arak branch, in  during 2013. Treatments composed of  without priming (control) and eleven  treatment compound as seed priming, foliar application, seed priming along with foliar application of  zinc sulfate and nano particle of zinc and seed priming with distillate water . The results showed that seed priming with distillate water and different sources of zinc increased the number of capitulum per plant as compared to control. Seed priming with distillate water and different methods of zinc sulfate application could be increased the 100 seed weight compared to nano particle of zinc. The maximum of number of grain per plant was obtained from seed priming with zinc sulfate treatments alone or along with foliar application and seed priming with 300 mg.L-1 nano particle of zinc. Seed priming with nano particle and zinc sulfate alone or along with foliar application increased grain yield compared with control. The maximum of grain yield equal to 2853.3 kg.ha-1 was observed from seed priming with 600 mg.L-1 along with 2 g.L-1 zinc sulphate.In general, the results showed thatseed priming with 300 mg.L-1 nano particle  or seed priming with 600 mg.L-1 along with 2 g.L-1  zinc sulphate can obtain acceptable product